Perkembangan Pendidikan Indonesia Pada Zaman Penjajahan II (Abad 20 Termasuk Masa Pendudukan Jepang) - Kusmawati , Heny; Najib, Misbah Khoirun; Rahmawati , Tina; Shofa, Dimas Ainus (Educationist: Journal of Educational and Cultural Studies, 2023)
Ethical politics focuses on building irrigation systems, organizing emigration and providing education to the Indonesian people. Ethical politics demands that the Indonesian people move towards progress, but remain under Dutch colonialism. Even though in reality ethical political policies do not necessarily bring prosperity to the Indonesian people, they are able to change the order of life of the nation, where irrigation systems are everywhere, people are familiar with modern agricultural and plantation systems. Emigration or transmigration, where people are sent outside Java, Indonesian people get to know each other and build good relationships. Education during the Dutch colonial period was initially only used to meet the needs of the Dutch in Indonesia. The education system of the Dutch colonial era was a complicated system because there were quite a lot of variations as a realization of the discrimination in the education system. The goals and educational political policies created and implemented by the Netherlands were solely for the benefit of the Dutch colonial government. Education during the Japanese colonial era, Indonesia experienced a decline in the field of education. When viewed from the side of education at that time, it was indeed very bad, while when viewed from the other side, the Japanese education system had a positive impact on Indonesia. This can be seen from the abolition of the class system (caste) which allows people from the lower middle class to go to school.